KARDIOCHIRURGIA DOROSŁYCHThe laboratory testing of different acetylsalicylic acid doses and the usefulness of plant polyphenol substances as antiplatelet supplementing therapy in patients after coronary artery bypass grafting surgery - Golański, Jacek; Golański, Ryszard; Kuliczkowski, Wiktor; Watała, Cezary (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Aim : The aim of the study was to assess the differences in laboratory antiplatelet effect of two acetylsalicylic acid (ASA) doses, 75 mg/d and 150 mg/d, in cardiovascular patients at 12 to 14 months after coronary artery bypass grafting (CABG). The other objective was to explore the idea that plant-derived polyphenol substances could supplement and compound the antiplatelet effect of ASA. Material and methods : The study included 55 patients (age 63.0 ±8.4 years) at 12-14 months after CABG, treated for that time with ASA at the dose of either 75 mg (24 pts) or 150 mg (31 pts) daily. The blood was incubated in vitro for 15 minutes with either Corvitin® or Aronox® to study their ability to block blood platelet reactivity. In order to investigate the antiplatelet effect of polyphenol substances we used optical aggregometry and TXB2 generation in plasma. To investigate the low laboratory ASA effect we monitored whole blood aggregometry and serum TXB2 concentration. Results : We observed higher TXB2 serum level in patients treated with 75 mg ASA/day in comparison with the 150 mg/d dose. Patients on a lower ASA dose had a higher rate of low laboratory ASA effect in comparison with patients on a higher ASA dose. We found that the antiplatelet effect of Aronox is present only in patients treated with the 75 mg ASA dose. Conclusions : In conclusion, to increase the antiplatelet effect in patients after CABG treated with a 75 mg dose of ASA, it can be proposed either to increase the ASA dose to 150 mg per day or to consider the use of dual therapy: low dose ASA (75 mg) supplemented with polyphenol substances.